LncRNA-miRNA-mRNA Network Analysis Reveals the Potential Biomarkers in Crohn’s Disease Rats Treated with Herb-Partitioned Moxibustion - Wang XJ; Li XY; Guo XC; Liu L; Jin YY; Lu YQ; Cao YJN; Long JY; Wu HG; Zhang D; Yang G; Hong J; et al. (Dove Medical Press, 2022)
Xue-Jun Wang,1,* Xiao-Ying Li,1,* Xiao-Cong Guo,1,* Li Liu,1 You-You Jin,1 Yun-Qiong Lu,1 Yao-Jia-Ni Cao,1 Jun-Yi Long,1 Huan-Gan Wu,2 Dan Zhang,2 Guang Yang,2 Jue Hong,2 Yan-Ting Yang,2 Xiao-Peng Ma1,2 1Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2Key Laboratory of Acupuncture-Moxibustion and Immunology, Shanghai Research Institute of Acupuncture and Meridian, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Peng Ma; Yan-Ting Yang, Key Laboratory of Acupuncture-Moxibustion and Immunology, Shanghai Research Institute of Acupuncture and Meridian, Shanghai, People's Republic of China, Email pengpengma@163.com; tcmyyt@126.comBackground: Long noncoding RNA (lncRNA) is receiving growing attention in Crohn's disease (CD). However, the mechanism by which herb-partitioned moxibustion (HPM) regulates the expression and functions of lncRNAs in CD rats is still unclear. The aim of our study is to identify lncRNA-miRNA-mRNA network potential biological functions in CD.Methods: RNA sequencing and microRNA (miRNA) sequencing were carried out to analyze lncRNA, miRNA and mRNA expression profiles among the CD rats, normal control rats, and CD rats after HPM treatment and constructed the potential related lncRNA-miRNA-mRNA competing endogenous RNA (ceRNA) networks. Then, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, protein-protein interaction (PPI) analysis and quantitative real-time polymerase chain reaction (qRT-PCR) were performed to explore potentially important genes in ceRNA networks.Results: A total of 189 lncRNAs, 32 miRNAs and 463 mRNAs were determined as differentially expressed (DE) genes in CD rats compared to normal control rats, and 161 lncRNAs, 12 miRNAs and 130 mRNAs were identified as remarkably DE genes in CD rats after HPM treatment compared to CD rats. GO analysis indicated that the target genes were most enriched in cAMP and in KEGG pathway analysis the main pathways included adipocytokine, PPAR, AMPK, FoxO and PI3K-Akt signaling pathway. Finally, qRT-PCR results confirmed that lncRNA LOC102550026 sponged miRNA-34c-5p to regulate the intestinal immune inflammatory response by targeting Pck1.Conclusion: By constructing a ceRNA network with lncRNA-miRNA-mRNA, PCR verification, and KEGG analysis, we revealed that LOC102550026/miRNA-34c-5p/Pck1 axis and adipocytokine, PPAR, AMPK, FoxO, and PI3K-Akt signaling pathways might regulate the intestinal immune-inflammatory response, and HPM may regulate the lncRNA LOC102550026/miR-34c-5p/Pck1 axis and adipocytokine, PPAR, AMPK, FoxO, and PI3K-Akt signaling pathways, thus improving intestinal inflammation in CD. These findings may be novel potential targets in CD.Keywords: herb-partitioned moxibustion, Crohn's disease, lncRNA, ceRNA, lncRNA LOC102550026/miR-34c-5p/Pck1 axis